Gastrointestinal stromal tumors with Kit gene mutation in 4 guinea pigs (Cavia porcellus). Issue 5 (September 2022) - Ueda, Kengo; Takanosu, Masamine; Kagawa, Yumiko; Ueda, Akiko; Ano, Naoko; Nomura, Kohji; Ozaki, Kiyokazu
Gastrointestinal stromal tumors (GISTs) have been rarely reported in guinea pigs. We aimed to characterize the clinical and pathological features of GISTs in 4 guinea pigs and investigate the presence of mutations in exon 11 of the KIT proto-oncogene receptor tyrosine kinase ( Kit ) gene. Two subjects were male and 2 were female; 2 were 6 years old, 1 was 7 years old, and 1 was of an unknown age. Three cases had primary gastric tumors, whereas 1 had a primary small intestinal tumor. All cases had tumors that extended from the submucosa to the serosa with extraluminal growth. A gastric tumor had gastric, pancreatic, and cecal metastases. Histologically, the tumors were sharply demarcated and composed of spindle cells arranged in bundles, intermixed with small amounts of collagenous stroma. The tumor cells had mild atypia with few mitotic figures (0–5/50 high power fields, 7.95 mm 2 ) and were immunolabeled for KIT and Discovered-on-GIST 1 ( DOG1 ). All cases had mutations in exon 11 of the Kit gene. These findings indicate that GISTs in guinea pigs are similar to those in humans and dogs. GISTs in guinea pigs are potentially malignant submucosal tumors with KIT- and DOG1-immunolabeling, exon 11 KIT mutations, and the possibility of metastasis.